"Proletarian Hegemony" in the Chinese Revolution and the Canton Commune of 1927 - Thomas, S. Bernard (Michigan Monographs In Chinese Studies, 2020)
The Communist aim of proletarian hegemony in the Chinese revolution was given concrete expression through the Canton Commune-reflected in the policies and strategies that led to the uprising, in the makeup and program of the Soviet setup in Canton, and in the subsequent assessment of the revolt by the Comintern and the Chinese Communist Party. "Proletarian Hegemony" in the Chinese Revolution and the Canton Commune of 1927 describes these developments and, with the further ideological treatment given the Commune serving as a backdrop, will then examine the continuing evolution and ultimate transformation of the proletarian line and the concept of proletarian leadership in the post-1927 history of Chinese Communism. [3]